Pengembangan Permainan Kosakata Interaktif Bahasa Jerman Level A1 Berbasis Aplikasi Construct 3 - Onyx Nifty; Elfretty Sitanggang; Yuni Melati Anestasya Simaremare; Roihan Anwar; Surya Yusuf; Surya Masniari Hutagalung (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to create Student Worksheets (LKS) using the Construct 3 application as a German vocabulary learning media at the A1 level for high school students. This study will employ a descriptive qualitative method. The process of creating the LKS utilizes Richey and Klein's theory, involving the following phases: (1) the planning phase, (2) the development or creation phase, and (3) evaluation phase. The data for this research consist of German vocabulary with themes "Hobbys" and "Die Familie" at A1 level, sourced from the book "Netzwerk neu A1 Kursbuch" published by Ernst Klett Sprachen GmbH in 2019. The application will be tested by media experts, and material testing will be conducted by native German speakers and instructional media specialists. The outcome of this research is a set of digital vocabulary games at A1 level for high school students and a book serving as teaching material for German vocabulary in high schools. The final output will be an article in a nationally and internationally indexed Journal or proceedings.